Expression of FoxP3, a key molecule in CD4CD25 regulatory T cells, in adult T-cell leukaemia/lymphoma cells - Karube, Kennosuke; Ohshima, Koichi; Tsuchiya, Takeshi; Yamaguchi, Takahiro; Kawano, Riko; Suzumiya, Junji; Utsunomiya, Atae; Harada, Mine; Kikuchi, Masahiro (British journal of haematology, 2004)
Adult T-cell leukaemia/lymphoma (ATLL) is an aggressive neoplastic disease that usually exhibits a CD4(+)CD25(+) phenotype. Regulatory T cells (Treg), which suppress T-cell effector function, are characterized by the co-expression of CD4 and CD25. We analysed the expression of forkhead/winged helix transcription factor (FoxP3), a specific marker that is important for the function of Treg, on ATLL cells from 17 patients (peripheral blood, n = 8; lymph node, n = 9). Real-time polymerase chain reaction and immunostaining detected FoxP3 expression in 10 ATLL cases, but was relatively down-regulated compared with Treg from normal subjects. These results indicate the association of ATLL and Treg.